Does the headquarter company regime still have a role to play in South African tax law and if so, which aspects of the regime require revision? - Gumula, Thuso (University of the Witwatersrand, Johannesburg, 2024)
The South African Headquarter Company Regime (HQC) was implemented on 1 January 2011, and it was designed to attract multinational companies to establish their headquarters in South Africa for the purpose of investing in other African nations through the country. Since the recommendations of the Katz Commission in 1997, the South African National Treasury (National Treasury) has done substantial work in terms of refining the provisions of the HQC regime to ensure that South Africa becomes an ideal Headquarter Company location. Since its inception in 2011 the HQC regime has failed to take off, with very few companies adopting the HQC regime. The South African HQC regime has been criticized for not being attractive to potential investors due to issues such as complicated qualifying requirements and the availability of alternative regimes such as Mauritius and Kenya, which are perceived as more appealing and user-friendly. The aim of this research is to assess whether the South African HQC regime remains relevant within South African tax legislation and, if it does, to identify which aspects of the HQC regime necessitate revision. This study will also include recommendations of proposed changes that can be made to address the current criticism of the HQC regime. The above objective will be achieved through literature review of applicable government publications, journal articles, tax articles from reputable websites, statutes etc.
A research report submitted to the Faculty of Commerce, Law, and Management in fulfillment of the requirements for the degree of Master of Commerce, School of Accountancy, University of the Witwatersrand, Johannesburg, 2024
Keywords: headquarter company; multinational companies; tax incentives; treaty shopping; International Headquarter Company regime; Katz Commission; Davis Tax Committee.; SDG-8: Decent work and economic growth